Resilience and fragility in global banking: Impacts on emerging economies - Marina Conesa; Giulia Lotti; Andrew Powell (Inter-American Development Bank (IDB), 2020)
Theory suggests both resilience and fragility in banking networks. This paper finds both, exploiting a new database of cross-border syndicated lending to developing countries from 1993 to 2017. Shocks propagate via co-lenders driven by central players, but shocks impacting fringe banks have little impact. The global financial crisis and the appearance of South-South lenders prompted a decline in network centrality, suggesting greater resilience to normal shocks. Multilateral Development Banks may play a catalytic role, but their small size limits their ability to mitigate shock propagation. The ongoing Covid-19 crisis is not a normal shock, is hitting central players and will likely provoke significant contagion.
Keywords: F34; G21; L14; 330; Syndicate loans; Shock propagation; Systemic banking crises; Banks